THE INFLUENCE OF WORK ENVIRONMENT TOWARDS TURNOVER INTENTION OF EMPLOYEE OF 4 STAR HOTELS IN PADANG CITY - Meirina, Ira; Ferdian, Feri; Pasaribu, Pasaribu; Suyuthie, Hijriyantomi (Institut Pariwisata dan Bisnis Internasional, 2018)
The purpose of this study was to analyze the influence of the work environment towards turnover intention of 4-star hotel employees in Padang City. This type of research is quantitative descriptive with a causal associative approach. The population in this study was 796 people consisting of all 4-star hotel employees in Padang City. The sample is 251 people using proportional random sampling technique. The data analysis technique used is simple linear regression analysis. The results of the study show that F counts with sig. 0,000 <0,05, then the work environment variable has a significant influence on employee turnover intention. Next, R Square is 0.309. This means that the work environment affects employee turnover intention by 30.9% and the rest is influenced by other factors such as salary, work stress, job satisfaction. Regression coefficient value if Y = a + bX = 17,713 + 0.744 X means that every increase of 1 unit of work environment will increase 0.744 employee turnover unit intention of 4-star hotel in Padang City.